Pemanfaatan Acces Right Oleh Pihak Asing Di Zona Ekonomi Eksklusif Indonesia - Hafiuddin, Ahmad; Presilia, Melany; Aprina, Elsa (Fakultas Hukum Universitas Bangka Belitung, 2024)
This study aims to review the access right provisions that can be utilized by oreign fishing vessels in the territory of Indonesia's Exclusive Economic Zone. Given that the provisions of UNCLOS 1982 provide an opportunity for other countries, especially for landlocked states and geographically disadvantaged states to take advantage of the Exclusive Economic Zone belonging to the coastal state. The research method used in writing this article is normative juridical. Based on the results of the study, the use of access right by foreign fishing vessels can be carried out based on konvention and must comply with national regulations of the Government of Indonesia, namely through Fisheries Act. Access rights can only be used by foreign parties if the coastal state has complied with the provisions stipulated in the convention and takes into account its national interest in food needs in the field of fisheries. So that the obligation of the coastal state in opening the access right as stated in the convention cannot necessarily be carried out if the Indonesian state government has not been optimal in implementing international and national regulations.